Interfacial Bonding of Metal‐Sulfides with Double Carbon for Improving Reversibility of Advanced Alkali‐Ion Batteries. (25th February 2020) - Ge, Peng; Zhang, Liming; Zhao, Wenqing; Yang, Yue; Sun, Wei; Ji, Xiaobo
Abstract: Engineering interfacial properties of metal‐sulfides toward excellent electrochemical capability is imperative for advanced energy‐storage materials. However, they still suffer from an unclear mechanism of capacity fading, along with ineffective physical–chemical evolution. Herein, a highly‐effective Sb2 S3 with double carbon is designed with interfacial SbC bonds and double carbon, which boosts promoting of ion transferring and alleviates the separation of both active phases (Sb, S). Through "voltage‐cutting" manners, the key elements of capacity improvement about phase transitions are further determined. As expected, even at 5.0 A g −1, the lithium‐storage capacity remains about 674 mAh g −1 . Utilized as sodium ion battery (SIB) anode, the rate capacity still reaches up to 366 mAh g −1 at 3.0 A g −1, much larger than that of Sb2 S3 . Obtaining the full cell of Ni–Fe Prussian blue analog versus M‐Sb2 S3 @DC, the reversible capacity is 330 mAh g −1 at 0.5 A g −1 . Supported by kinetic analysis, the excellent rate properties are determined by the surface‐controlling behaviors, mainly resulting from the decreased capacitive resistance and improved ion moving. Furthermore, the reassembling evolution of active phases is revealed in detail by ex situ techniques. This work is expected to offer significant insights into interfacial evolutions toward advanced energy‐storage systems. Abstract : M‐Sb2 S3 @DCs with SbC bonds and double carbon are well designed through a thermal chemical process. It is found that the mechanism of capacity fading is the separation of two phases (Sb, S), which can be controlled by the evolution of physical–chemical properties. This work is expected to offer significant insights into interfacial evolutions toward advanced energy‐storage systems.